THE CIVIL LAW PERSPECTIVE ON LEGAL CONSEQUENCES OF SAFEGUARDING CONSUMER PERSONAL DATA IN INDONESIAN E-COMMERCE ACTIVITIES - Purnomo, Mahendra Bisma Wisdha Wardana; Rijadi, Prof. Dr. Prasetijo (YURIS: Journal of Court and Justice, 2024)
The rapid evolution of digital technologies in the early decades of the 2000s has significantly transformed commerce, with e-commerce emerging as a dominant platform for transactions in Indonesia. This digital shift, while enhancing efficiency and accessibility, has raised critical legal and ethical concerns surrounding the safeguarding of consumers' personal information. In response, the Indonesian state has enacted several normative instruments, such as Law No. 11 of 2008 concerning Electronic Information and Transactions, Government Regulation No. 80 of 2019, Ministerial Regulation No. 20 of 2016, Government Regulation No. 71 of 2019, and Law No. 27 of 2022 concerning the Protection of Personal Data. This research aims to analyze the legal structure that regulates the safeguarding of personal data within Indonesian e-commerce, employing a normative juridical approach, which analyzes statutory provisions and legal theories without relying on empirical data. The study finds that while Indonesia has made notable progress in establishing regulations, challenges persist in enforcement, supervision, and public awareness. Weak implementation and limited legal remedies leave consumers susceptible to unauthorized access and exploitation of personal information. Therefore, there is a need for a harmonized, implementable, and accountable legal regime to guarantee comprehensive protection of personal data within the context of the digital economy. Strengthening institutional capacity, improving legal certainty, and ensuring accessible mechanisms for dispute resolution are essential steps toward building consumer trust and promoting accountability among digital platform providers. This study concludes that a robust legal system is critical for securing consumer rights and advancing ethical practices in Indonesia’s rapidly expanding e-commerce sector.